Toxicological evaluation of imidazo-based heterocyclic derivatives: In-vitro and in-vivo acute toxicity studies - Sunil Kumar; Ajay Singhal; Pankaj Kumar; Manish Jain; Manpreet Kaur; Ishika Gupta; Deepak B. Salunke; Sandip V. Pawar (Toxicology Reports, 2025)
Imidazo based heterocyclic derivatives are considered as privileged scaffolds due to their presence in various pharmacologically active compounds and in marketed formulations. The present study reports toxicological evaluation of three imidazo based heterocyclic derivatives which are currently being investigated for their potential anticancer activity. Compounds IG-01–007, IG-01–008, and IG-01–009 were assessed for cytotoxicity, hemolysis, and DNA fragmentation activity. Acute oral toxicity studies were performed at doses of 300 mg/kg and 1000 mg/kg according to OECD guidelines, in both male and female Wistar rats. All test compounds at a concentration of 50 µM resulted in DNA fragmentation suggesting notable impact on DNA integrity. The in-vivo acute toxicity study indicated significant toxicity at doses of ≥ 1000 mg/kg, particularly for compounds IG-01–008 and IG-01–009, which caused hepatic damage and cholestasis in liver tissues. These results collectively suggest that imidazo based heterocyclic derivatives used in the present study exhibit cytotoxic potential.